Preparation method of normal-temperature ultra-wide spectrum self-driven photoelectric detector based on Bi0. 07Sn0. 93S

By using Bi0.07Sn0.93S material and high vacuum sealing equipment and other technologies, an ultra-wide spectrum self-driven photodetector capable of efficiently detecting ultraviolet, visible light and near-infrared spectrum at zero bias voltage at room temperature was prepared, solving the problem of limited detection range in the prior art.

CN119907331AActive Publication Date: 2025-04-29INST OF PHYSICS HENAN ACAD OF SCI +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411754404.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-29
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing ultra-wide spectrum self-driven photodetectors are difficult to detect ultraviolet, visible light and near-infrared spectra efficiently at room temperature and zero bias voltage.

Method used

Bi0.07Sn0.93S material was used to prepare Bi0.07Sn0.93S nanosheets through high vacuum sealing equipment and PDMS dry transfer technology. Combined with the temperature control of a dual-temperature zone tube furnace and metal evaporation technology, an ultra-wide spectrum self-driven photodetector was prepared.

Benefits of technology

It achieves a good response to the 265nm-1550nm spectral range under normal temperature zero bias conditions, improving the performance and application range of the photodetector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907331A_ABST
    Figure CN119907331A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a normal-temperature ultra-wide spectrum self-driven photoelectric detector based on Bi0. 07Sn0. 93S, and belongs to the field of semiconductor devices. The preparation method of the Bi0. 07Sn0. 93S single crystal comprises the following steps: growing a large-size Bi0. 07Sn0. 93S single crystal by adopting a chemical vapor transport method, obtaining a 2D Bi0. 07Sn0. 93S nanosheet by using mechanical stripping, then transferring the 2D Bi0. 07Sn0. 93S nanosheet to a SiO2 / Si substrate by using a dry transfer technology and a two-dimensional transfer platform, etching two electrode patterns, and then evaporating a metal layer through a high-vacuum thermal evaporation deposition system, thereby obtaining the Bi0. 07Sn0. 93S single crystal. And the 2D Bi0. 07Sn0. 93S nanosheet ultra-wide spectrum self-driven photoelectric detection device is obtained. A photoelectric detector based on the 2D Bi0. 07Sn0. 93S nanosheet shows good ultra-wide spectral response under the conditions of normal temperature and zero bias voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of semiconductor devices, and specifically relates to a semiconductor device based on Bi 0.07 Sn 0.93 S Preparation method of room temperature ultra-wide spectrum self-driven photoelectric detector. Background Art

[0002] Ultra-wide spectrum self-driven photodetectors can process light signals of different bands simultaneously, so as to better detect and identify targets. They have important applications in astronomy, biological diagnosis, land cover classification and three-dimensional surface reconstruction. At present, ultra-wide spectrum self-driven photodetectors are mainly based on epitaxially grown semiconductor InP, HgCdTe and II superlattice materials. However, these materials have low yields, complex manufacturing processes and high costs, which limits their applications. Therefore, exploring new ultra-wide spectrum light absorption materials has become an important goal.

[0003] Emerging two-dimensional layered semiconductor materials have gradually become ideal materials for building photodetectors due to their excellent optoelectronic properties, atomic layer thickness, adjustable band gap, and good complementary metal oxide semiconductor process compatibility. For example, bP, MoTe2, GeSe, etc. have been shown to have great application prospects in visible light and near-infrared light detection. Compared with other two-dimensional layered semiconductor materials, SnS crystals have been shown to have good optoelectronic properties in the near-infrared spectrum due to their narrow band gap. However, so far, the band gap can be regulated within a certain range by changing the number of layers, stress, etc., but the regulation is limited, and the detection range of the SnS-based photodetector is difficult to cover the ultraviolet, visible light, and infrared light spectra at the same time. By replacing doping with elements such as V, Fe, Nb and Ta, the band structure, phonon vibration, lattice symmetry and carrier transport can be regulated within a certain range. Therefore, how to use the method of atomic substitution doping of SnS nanosheets to develop room-temperature ultra-wide spectrum self-driven photodetectors is of great significance. Summary of the invention

[0004] The purpose of the present invention is to provide a Bi-based detector to solve the key technical problem that a single device cannot efficiently detect ultraviolet, visible light and near-infrared light at room temperature and zero bias. 0.07 Sn 0.93 S Preparation method of room temperature ultra-wide spectrum self-driven photoelectric detector.

[0005] The purpose of the present invention is achieved through the following solutions:

[0006] A Bi-based 0.07 Sn 0.93 The method for preparing a room temperature ultra-wide spectrum self-driven photoelectric detector comprises the following steps:

[0007] S1: Weigh a certain amount of Bi powder, Sn powder and S powder, wherein the mass ratio of Bi powder, Sn powder and S powder is 1:1:2, and then weigh 10-20 mg of iodine particles, mix them evenly and transfer them into an ampoule bottle;

[0008] S2: Use high vacuum sealing equipment to make the vacuum degree in the ampoule bottle less than 4×10 -3 Pa, oxygen content is less than 3ppm, and the speed of the ampoule is maintained at 2-5r / min during the hot melt sealing process;

[0009] S3: Place the hot-melt sealed ampoule bottle flat in a dual-temperature zone tube furnace and set the temperature of the dual-temperature zone tube furnace; obtain a large-size Bi with metallic luster in the reaction zone. 0.07 Sn 0.93 S single crystal;

[0010] S4 uses PDMS dry transfer technology and two-dimensional material transfer platform to transfer mechanically exfoliated 2D Bi 0.07 Sn 0.93 S nanosheets transferred to SiO2 / Si substrate;

[0011] S5: The electrode pattern is prepared through the steps of coating, pre-baking, exposure, development, fixing, post-baking, etc.

[0012] S6: Using a thermal evaporation coating apparatus to evaporate metal onto the surface of the photoresist, and using a lift-off process to peel off the metal film;

[0013] S7: Use aluminum wire spot welding machine to weld the lead wire to complete the 2D Bi 0.07 Sn 0.93 Preparation of S nanosheet ultra-wide spectrum self-driven photodetection devices.

[0014] Furthermore, the Bi powder is of 5N grade with a particle size of 200 nm, the Sn powder is of 5N grade with a particle size of 200 nm, the S powder is of 5N grade with a particle size of 100 nm, the purity of the Bi powder, Sn powder and S powder is not less than 99.999%, and the purity of the iodine particles is required to be analytically pure.

[0015] Further, in step S3, the temperature of the dual-temperature zone tube furnace is set as follows: the temperature of the reaction zone is increased to 450°C at a rate of 2-4°C / min and kept for 60 minutes, then increased to 720°C at 4-5°C / min and maintained for 4380 minutes. The temperature of the growth zone is increased to 450°C at a rate of 2-4°C / min and kept for 60 minutes, then increased to 750°C at 4-5°C / min and maintained for 1440 minutes, and then the growth zone is cooled to 520°C at a cooling rate of 7-8°C / min and maintained for 2500-3000 minutes.

[0016] Further, step S4 is specifically as follows:

[0017] S41: Glue the PDMS polymer film onto a transparent glass slide, making sure the surface is flat and free of bubbles.

[0018] S42: Use mechanical peeling tool to peel off Bi on PDMS polymer film 0.07 Sn 0.93 S single crystal nanosheets.

[0019] S43: Flip the PDMS polymer film with the nanosheets and fix it in mid-air on a glass slide of a two-dimensional material transfer platform.

[0020] S44: With the assistance of the microscopic imaging system, adjust the slide displacement platform to align the nanosheets on the PDMS polymer film with the SiO2 / Si substrate. Slowly lower the cantilever height to fully contact and press the PDMS polymer film with the target substrate.

[0021] S45: Slowly lift the cantilever to achieve bonding of the nanosheet and the SiO2 / Si substrate.

[0022] S46: Repeat steps S41-S45 to obtain a first nanosheet layer of 100-150 nm on the SiO2 / Si substrate; continue to repeat steps S41-S45 to prepare a second nanosheet layer of 20-30 nm thickness on the surface of the first nanosheet layer to obtain an initial sample.

[0023] Furthermore, step S5 is specifically as follows:

[0024] S51: Gluing

[0025] Place the initial sample on the suction cup of the glue spreader and turn on the vacuum pump to suck the substrate; use a dropper or automatic glue dropper to add an appropriate amount of photoresist to the center of the second nanosheet layer; first rotate at a low speed of 500-700r / min for 5-10s to spread the photoresist evenly on the surface of the nanosheet, and then rotate at a high speed of 3000-6000r / min for 30-50s to allow the photoresist to form a uniform film.

[0026] S52: Pre-baking

[0027] Place the substrate coated with photoresist on a hot plate for pre-baking. The temperature is set at 100-120°C and the baking time is 1-5 minutes to remove the solvent in the photoresist and solidify the photoresist.

[0028] S53: Exposure

[0029] Put the substrate with the cured photoresist into the photolithography machine, align the designed electrode pattern mask with the substrate, use a mercury lamp as the light source, and the exposure time is 10-30s to make the photoresist undergo a photochemical reaction in the light-transmitting area of ​​the mask.

[0030] S54: Development

[0031] After exposure, the substrate is placed in a developer solution for 60-100 seconds.

[0032] S55: Fixing

[0033] Soak the sample in fixative for 10-50 minutes.

[0034] S56: Post-baking

[0035] The fixed sample is post-baked at a temperature of 120-160° C. for 5-8 minutes to further solidify the photoresist pattern, enhance the adhesion between the photoresist and the substrate, and make the electrode pattern more stable.

[0036] Further, in step S6, the substrate with the photoresist pattern is placed in the chamber of the thermal evaporation coating apparatus, the sample is fixed, and the vacuum degree of the chamber is 3×10 -4 -5×10 -4 Pa, firstly, a layer of Au or Ag is evaporated on the surface of the photoresist, and then a layer of Cr is evaporated on the surface of the Au or Ag layer, wherein the evaporation rate of Au or Ag is: Cr deposition rate: The thickness of the Au layer or the Ag layer is 40-50 nm, and the thickness of the Cr layer is 4-6 nm.

[0037] After the coating is completed, the sample is taken out of the coating machine and immersed in acetone or N-methylpyrrolidone. The photoresist is dissolved by the solvent, and the metal film on it is peeled off because there is no support from the underlying photoresist, while the metal under the photoresist-covered area remains on the substrate, thus forming the desired metal pattern. The sample is then rinsed with a solvent to remove the remaining photoresist and metal fragments, and then dried.

[0038] The method of the present invention has the following advantages:

[0039] 1. This method uses iodine particles as a gas delivery agent, which can effectively reduce Bi 0.07 Sn 0.93 The reaction activation energy of S enables the reaction to occur at a temperature lower than the metal melting point of Bi in the gas phase reaction, thereby inhibiting Sn+S→SnS and Bi+S→SnS.

[0040] 2. Compared with the prior art, before reaching the growth temperature of 520°C, the temperature of the growth zone is 750°C, which is higher than the temperature of the reaction zone of 720°C, so that the source can fully volatilize and react. 0.07 Sn 0.93 The size and quality of the single crystal of S are adjusted by step S4. In addition, the photosensitive layer 2DBi contacting the source and drain electrodes is regulated 0.07Sn 0.93 The thickness difference of S nanosheets and the interface state lead to the difference in Schottky barrier height, forming a built-in electric field, which realizes the preparation of ultra-wide spectrum self-driven photodetector.

[0041] 3. By introducing Bi element into SnS binary material, the bandgap width can be adjusted. The mass ratio of Bi powder, Sn powder and S powder is set to 1:1:2, and the heating rate and temperature value in the dual temperature zone are set. 0.07 Sn 0.93 The single crystal size of S is larger.

[0042] 4. This application is based on 2D Bi 0.07 Sn 0.93 The S nanosheet photodetector exhibits good ultra-wide spectral response (265nm-1550nm) under room temperature and zero bias conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Bi in the present invention 0.07 Sn 0.93 Schematic diagram of the S single crystal growth process.

[0044] Figure 2 Bi in the present invention 0.07 Sn 0.93 S single crystal growth temperature curve.

[0045] Figure 3 Bi in the present invention 0.07 Sn 0.93 S single crystal optical image.

[0046] Figure 4 is the 2D Bi 0.07 Sn 0.93 Schematic diagram of S photodetector.

[0047] Figure 5 is the 2D Bi 0.07 Sn 0.93 Actual picture of S photodetector.

[0048] Figure 6 is the 2D Bi 0.07 Sn 0.93 S photodetector wavelength response spectrum.

[0049] Figure 7 is the 2D Bi 0.07 Sn 0.93 Photocurrent spectrum of the S photodetector at zero bias.

[0050] Figure 8is the 2D Bi 0.07 Sn 0.93 S is the surface potential difference of the photodetector device.

[0051] Fig. 9 is the 2D Bi 0.07 Sn 0.93 Diagram of the self-driven photodetection mechanism of S photodetector. DETAILED DESCRIPTION

[0052] The present invention will be further described below in conjunction with embodiments:

[0053] Example 1

[0054] A Bi-based 0.07 Sn 0.93 The method for preparing a room temperature ultra-wide spectrum self-driven photoelectric detector comprises the following steps:

[0055] S1: Weigh 0.1g Bi powder, 0.1g Sn powder and 0.2g S powder, and then weigh 10mg iodine granules, mix them evenly and transfer them into an ampoule;

[0056] S2: Use high vacuum sealing equipment to make the vacuum in the ampoule bottle 1×10 -3 Pa, oxygen content 1ppm, the ampoule bottle maintained a rotation speed of 5r / min during the hot melt sealing process;

[0057] S3: Place the hot-melt sealed ampoule bottle flat in a dual-zone tubular furnace. The temperature of the dual-zone tubular furnace is set as follows: the temperature of the reaction zone is increased to 450°C at a rate of 2°C / min and kept for 60 minutes, then increased to 720°C at 4°C / min and maintained for 4380 minutes. The temperature of the growth zone is increased to 450°C at a rate of 2°C / min and kept for 60 minutes, then 4.2°C / min to 750°C and maintained for 1440 minutes, and then the growth zone is cooled to 520°C at a cooling rate of 7.7°C / min and maintained for 2880 minutes. Large-sized Bi with metallic luster is obtained in the reaction zone. 0.07 Sn 0.93 S single crystal;

[0058] S4: PDMS dry transfer technology and two-dimensional transfer platform were used to transfer the mechanically exfoliated 2DBi 0.07 Sn 0.93 S nanosheets transferred to SiO2 / Si substrate;

[0059] S41: Glue the PDMS polymer film onto a transparent glass slide, making sure the surface is flat and free of bubbles.

[0060] S42: Use mechanical peeling tool to peel off Bi on PDMS polymer film 0.07 Sn0.93 S single crystal nanosheets.

[0061] S43: Flip the PDMS polymer film with the nanosheets and fix it in mid-air on a glass slide of a two-dimensional material transfer platform.

[0062] S44: With the assistance of the microscopic imaging system, adjust the slide displacement platform to align the nanosheets on the PDMS polymer film with the SiO2 / Si substrate. Slowly lower the cantilever height to fully contact and press the PDMS polymer film with the target substrate.

[0063] S45: Slowly lift the cantilever to achieve bonding of the nanosheet and the SiO2 / Si substrate.

[0064] S46: Repeat steps S41-S45 to obtain a first nanosheet layer of 100 nm on the SiO2 / Si substrate; continue to repeat steps S41-S45 to prepare a second nanosheet layer of 20 nm thickness on the surface of the first nanosheet layer.

[0065] S5: The electrode pattern is prepared through the steps of coating, pre-baking, exposure, development, fixing, post-baking, etc.

[0066] S6: Using a thermal evaporation coating apparatus to evaporate metal onto the surface of the photoresist, and using a lift-off process to peel off the metal film;

[0067] Place the substrate with the photoresist pattern into the chamber of the thermal evaporation coating instrument and fix the sample. The vacuum degree of the chamber is 3×10 -4 Pa, firstly, a layer of Au is evaporated on the surface of the photoresist, and then a layer of Cr is evaporated on the surface of the Au layer, wherein the evaporation rate of Au is: Cr deposition rate: The thickness of the Au layer is 40 nm, and the thickness of the Cr layer is 4 nm.

[0068] S7: Use aluminum wire spot welding machine to weld the lead wire to complete the 2D Bi 0.07 Sn 0.93 Preparation of S nanosheet ultra-wide spectrum self-driven photodetection devices.

[0069] Example 2

[0070] A Bi-based 0.07 Sn 0.93 The method for preparing a room temperature ultra-wide spectrum self-driven photoelectric detector comprises the following steps:

[0071] S1: Weigh 0.1g Bi powder, 0.1g Sn powder and 0.2g S powder, and then weigh 15mg iodine granules, mix them evenly and transfer them into an ampoule;

[0072] S2: Use high vacuum sealing equipment to make the vacuum in the ampoule bottle 3×10 -3 Pa, oxygen content is 2ppm, and the speed of the ampoule is maintained at 3r / min during the hot melt sealing process;

[0073] S3: Place the hot-melt sealed ampoule bottle flat in a dual-temperature zone tube furnace. The temperature of the dual-temperature zone tube furnace is set as follows: the temperature of the reaction zone is increased to 450°C at a rate of 3°C / min and kept for 60 minutes, then increased to 720°C at 4.5°C / min and maintained for 4380 minutes. The temperature of the growth zone is increased to 450°C at a rate of 3°C / min and kept for 60 minutes, then increased to 750°C at 4.5°C / min and maintained for 1440 minutes, and then the growth zone is cooled to 520°C at a cooling rate of 7°C / min and maintained for 2880 minutes. Large-sized Bi with metallic luster is obtained in the reaction zone. 0.07 Sn 0.93 S single crystal;

[0074] S4: PDMS dry transfer technology and two-dimensional transfer platform were used to transfer the mechanically exfoliated 2DBi 0.07 Sn 0.93 S nanosheets transferred to SiO2 / Si substrate;

[0075] S41: Glue the PDMS polymer film onto a transparent glass slide, making sure the surface is flat and free of bubbles.

[0076] S42: Use mechanical peeling tool to peel off Bi on PDMS polymer film 0.07 Sn 0.93 S single crystal nanosheets.

[0077] S43: Flip the PDMS polymer film with the nanosheets and fix it in mid-air on a glass slide of a two-dimensional material transfer platform.

[0078] S44: With the assistance of the microscopic imaging system, adjust the slide displacement platform to align the nanosheets on the PDMS polymer film with the SiO2 / Si substrate. Slowly lower the cantilever height to fully contact and press the PDMS polymer film with the target substrate.

[0079] S45: Slowly lift the cantilever to achieve bonding of the nanosheet and the SiO2 / Si substrate.

[0080] S46: Repeat steps S41-S45 to obtain a first nanosheet layer of 120 nm on the SiO2 / Si substrate; continue to repeat steps S41-S45 to prepare a second nanosheet layer of 25 nm thickness on the surface of the first nanosheet layer.

[0081] S5: The electrode pattern is prepared through the steps of coating, pre-baking, exposure, development, fixing, post-baking, etc.

[0082] S6: Using a thermal evaporation coating apparatus to evaporate metal onto the surface of the photoresist, and using a lift-off process to peel off the metal film;

[0083] Place the substrate with the photoresist pattern into the chamber of the thermal evaporation coating instrument and fix the sample. The vacuum degree of the chamber is 4×10 -4 Pa, firstly, a layer of Au is evaporated on the surface of the photoresist, and then a layer of Cr is evaporated on the surface of the Au layer, wherein the evaporation rate of Au is: Cr deposition rate: The thickness of the Au layer is 45 nm, and the thickness of the Cr layer is 5 nm.

[0084] S7: Use aluminum wire spot welding machine to weld the lead wire to complete the 2D Bi 0.07 Sn 0.93 Preparation of S nanosheet ultra-wide spectrum self-driven photodetection devices.

[0085] Example 3

[0086] A Bi-based 0.07 Sn 0.93 The method for preparing a room temperature ultra-wide spectrum self-driven photoelectric detector comprises the following steps:

[0087] S1: Weigh 0.1g Bi powder, 0.1g Sn powder and 0.2g S powder, and then weigh 20mg iodine granules, mix them evenly and transfer them into an ampoule;

[0088] S2: Use high vacuum sealing equipment to make the vacuum degree in the ampoule bottle 2×10 -3 Pa, oxygen content 1ppm, the ampoule bottle maintained a rotation speed of 2r / min during the hot melt sealing process;

[0089] S3: Place the hot-melt sealed ampoule bottle flat in a dual-zone tube furnace. The temperature of the dual-zone tube furnace is set as follows: the temperature of the reaction zone is increased to 450°C at a rate of 4°C / min and kept for 60 minutes, then increased to 720°C at 5°C / min and maintained for 4380 minutes. The temperature of the growth zone is increased to 450°C at a rate of 4°C / min and kept for 60 minutes, then increased to 750°C at 4.8°C / min and maintained for 1440 minutes, and then the growth zone is cooled to 520°C at a cooling rate of 8°C / min and maintained for 3000 minutes. Large-sized Bi with metallic luster is obtained in the reaction zone. 0.07 Sn 0.93 S single crystal;

[0090] S4: PDMS dry transfer technology and two-dimensional transfer platform were used to transfer the mechanically exfoliated 2DBi 0.07 Sn 0.93 S nanosheets transferred to SiO2 / Si substrate;

[0091] S41: Glue the PDMS polymer film onto a transparent glass slide, making sure the surface is flat and free of bubbles.

[0092] S42: Use mechanical peeling tool to peel off Bi on PDMS polymer film 0.07 Sn 0.93 S single crystal nanosheets.

[0093] S43: Flip the PDMS polymer film with the nanosheets and fix it in mid-air on a glass slide of a two-dimensional material transfer platform.

[0094] S44: With the assistance of the microscopic imaging system, adjust the slide displacement platform to align the nanosheets on the PDMS polymer film with the SiO2 / Si substrate. Slowly lower the cantilever height to fully contact and press the PDMS polymer film with the target substrate.

[0095] S45: Slowly lift the cantilever to achieve bonding of the nanosheet and the SiO2 / Si substrate.

[0096] S46: Repeat steps S41-S45 to obtain a first nanosheet layer of 150 nm on the SiO2 / Si substrate; continue to repeat steps S41-S45 to prepare a second nanosheet layer of 30 nm thickness on the surface of the first nanosheet layer.

[0097] S5: The electrode pattern is prepared through the steps of coating, pre-baking, exposure, development, fixing, post-baking, etc.

[0098] S6: Using a thermal evaporation coating apparatus to evaporate metal onto the surface of the photoresist, and using a lift-off process to peel off the metal film;

[0099] Place the substrate with the photoresist pattern into the chamber of the thermal evaporation coating instrument and fix the sample. The vacuum degree of the chamber is 5×10 -4 Pa, first evaporate a layer of Ag on the surface of the photoresist, and then evaporate a layer of Cr on the surface of the Ag layer, where the evaporation rate of Ag is Cr deposition rate: The thickness of the Ag layer is 50 nm, and the thickness of the Cr layer is 6 nm.

[0100] S7: Use aluminum wire spot welding machine to weld the lead wire to complete the 2D Bi 0.07 Sn 0.93 Preparation of S nanosheet ultra-wide spectrum self-driven photodetection devices.

Claims

1. A Bi-based 0.07 Sn 0.93 The method for preparing a room temperature ultra-wide spectrum self-driven photoelectric detector is characterized in that: The steps include: S1: Weigh a certain amount of Bi powder, Sn powder and S powder, wherein the mass ratio of Bi powder, Sn powder and S powder is 1:1:2, and then weigh 10-20 mg of iodine particles, mix them evenly and transfer them into an ampoule bottle; S2: Use high vacuum sealing equipment to make the vacuum degree in the ampoule bottle less than 4×10 -3 Pa, oxygen content is less than 3ppm, and the speed of the ampoule is maintained at 2-5r / min during the hot melt sealing process; S3: Place the hot-melt sealed ampoule bottle flat in a dual-temperature zone tube furnace and set the temperature of the dual-temperature zone tube furnace; obtain a large-size Bi with metallic luster in the reaction zone. 0.07 Sn 0.93 S single crystal; S4: PDMS dry transfer technology and two-dimensional material transfer platform were used to transfer the mechanically exfoliated 2D Bi 0.07 Sn 0.93 S nanosheets transferred to SiO2 / Si substrate; S5: The electrode pattern is prepared through the steps of coating, pre-baking, exposure, development, fixing, post-baking, etc. S6: Using a thermal evaporation coating apparatus to evaporate metal onto the surface of the photoresist, and using a lift-off process to peel off the metal film; S7: Use aluminum wire spot welding machine to weld the lead wire to complete 2DBi 0.07 Sn 0.93 Preparation of S nanosheet ultra-wide spectrum self-driven photodetection devices.

2. The method for preparing a self-driven photodetector according to claim 1, characterized in that: The Bi powder is of 5N grade with a particle size of 200nm, the Sn powder is of 5N grade with a particle size of 200nm, the S powder is of 5N grade with a particle size of 100nm, and the purity of the iodine particles is required to be analytical grade.

3. The method for preparing a self-driven photodetector according to claim 2, characterized in that: In step S3, the temperature of the dual-zone tubular furnace is set as follows: the temperature of the reaction zone is increased to 450°C at a rate of 2-4°C / min and kept for 60 minutes, then increased to 720°C at 4-5°C / min and maintained for 4380 minutes; the temperature of the growth zone is increased to 450°C at a rate of 2-4°C / min and kept for 60 minutes, then increased to 750°C at 4.2°C / min and maintained for 1440 minutes, and then the growth zone is cooled to 520°C at a cooling rate of 7-8°C / min and maintained for 2500-3000 minutes.

4. The method for preparing a self-driven photodetector according to claim 3, characterized in that: Step S4 is specifically as follows: S41: Adhere the PDMS polymer film to a transparent glass sheet, ensuring that the surface is flat and free of bubbles; S42: Use mechanical peeling tool to peel off Bi on PDMS polymer film 0.07 Sn 0.93 S single crystal nanosheets; S43: Flip the PDMS polymer film with nanosheets and fix it in mid-air on a glass slide of a two-dimensional material transfer platform; S44: With the assistance of the microscopic imaging system, the slide displacement platform is adjusted to align the nanosheets on the PDMS polymer film with the SiO2 / Si substrate, and the cantilever height is slowly lowered to fully contact and press the PDMS polymer film with the target substrate; S45: slowly lifting the cantilever to achieve bonding of the nanosheet and the target substrate; S46: Repeat steps S41-S45 to obtain a first nanosheet layer of 100-150 nm on the SiO2 / Si substrate; continue to repeat steps S41-S45 to prepare a second nanosheet layer of 20-30 nm thickness on the surface of the first nanosheet layer.

Citation Information

Patent Citations

  • Self-junction photoelectric detector based on molecular beam epitaxy technology and preparation method thereof

    CN111933738A

  • Broadband photoelectric detector based on novel two-dimensional topological material and preparation method thereof

    CN116314387A

  • Two-dimensional transition metal chalcogenide nanosheet and powder intercalation preparation method and application thereof

    CN118619346A

  • Radar sensor with waveguide structure

    KR1020240032644A

  • Mid and far-infrared nanocrystals based photodetectors with enhanced performances

    US20200083469A1